방사선과 신입생의 기초 수리능력 수준에 대한 연구 - 장현철; Hyon Chol Jang; 조평곤; Pyong Kon Cho (한국방사선학회 논문지, 2020)
4차 산업 혁명 시대에 가상현실(VR), 인공지능(AI) 등에 있어서 더욱더 수리 능력을 요구하고 있다. 이에 본 연구는 2019년 6월 17일에서 28일까지 S와 D 대학교 방사선학과 신입생 총 78명을 대상으로 기초학습수리영역 진단 평가를 통해 기초 수리능력에 대한 수준을 파악하여 기초자료를 마련하고자 하였다. 연구결과, 대학생들의 기초 수리능력의 수준은 전반적으로 우수한 것으로 진단되었으나, 기하와 벡터 평균점수 2.61점, 확률과 통계 평균점수 2.64점으로 보통 수준 진단되어 다른 영역보다 낮게 나타났다. 성별에 따른 기초수리능력 수준은 남학생 평균점수 17.48점, 여학생 16.29점으로 우수 수준으로 진단되었으며, 통계적으로는 유의한 차이가 없었다(p>0.05). 본 연구는 적은 연구대상 인원과 지역적인 제한점이 있기에 연구결과를 전체 대학교 신입생 및 모들 학과에 대해 일반화하는데 있어 다소 한계가 있을 수 있다. 이상의 결과를 토대로, 방사선학과 입학한 신입생들의 기초 수리능력 향상을 위해 학생 수준별로 전공과 관련된 기초 수리능력에 대한 향상 특강 등 다양한 프로그램이 진행 될 필요가 있으며, 교육과정에 전공 수학 교과목을 개설하여 학생 수준에 맞는 교수 학습방법 적용하여 수리능력에 대한 역량을 강화 할 필요가 있다. The era of the Fourth Industrial Revolution is increasingly demanding mathematical competencies for virtual reality (VR), artificial intelligence (AI) and the like. In this context, this study intended to identify the basic mathematical competency levels of university freshman students in radiology department and to provide basic data thereon. For this, the diagnostic assessment of basic learning competencies for the domain of mathematics was conducted from June 17, 2019 to June 28, 2019 among 78 freshman students of radiology department at S university and D university. As a result, the university students' overall basic mathematical competency levels were diagnosed to be excellent. However, their levels in the sectors of the geometry and vector and the probability and statistics were diagnosed to be moderate, with the mean scores of 2.61 points and 2.64 points, respectively, which were found to be lower than those of the other sections. As for basic mathematical competency levels according to genders, the levels of male students and female students were diagnosed to be excellent, with the mean scores of 17.48 points and 16.29 points, respectively, showing no statistically significant difference (p>0.05). Given the small number of subjects and regional restriction, there might be some limitations in the generalization of the findings of the present study to all university freshman students and all departments. The above results suggest that it is necessary to implement various programs such as student level-based special lectures for enhancing basic mathematical competencies relating to major in order to improve the basic mathematical competencies of freshman students in radiology department, and that it is necessary to increase the students' mathematical competencies by offering major math courses in the curriculum and applying teaching-learning methods matching students' levels.